Managing return on investment : implications for pricing, volume, and funds flow - Manners, George E.; Louderback, Joseph G. (Lexington, Mass. : Lexington Books, 1981)
This book is for managers who use return on investment (ROI), or who would like to, in making decisions regarding price, volume, investment, and a host of other factors like credit terms and inventory policy.
Includes index.
Includes bibliographical references and index
hza 23/08/2018
Loans
Keywords: Capital investments; Rate of return